USE OF AUTOMATED BALL INDENTATION METHOD TO EVALUATE THE FRACTURE TOUGHNESS OF Q235B STEEL - ZHANG GuoXin; WANG WeiQiang; WANG Shang (Jixie qiangdu)
The automated ball indentation method（ ABI） which is a new way to evaluate the mechanical properties of the materials has been studied in recent years. In order to explore the applicability of the ABI method to evaluate the fracture toughness of metallic materials,some ABI tests were performed by using the Q235B steel. The fracture toughness got from the ABI tests were compared with that from the conventional fracture tests. The results of comparison show that the error between the two methods was less than 10%. As a result,the ABI method can be used to evaluate the fracture toughness of the Q235B steel.